Efficacy and safety of CT-P47 versus reference tocilizumab: 32-week results of a randomised, active-controlled, double-blind, phase III study in patients with rheumatoid arthritis, including 8 weeks of switching data from reference tocilizumab to CT-P47 - Smolen, Josef S; Trefler, Jakub; Racewicz, Artur; Jaworski, Janusz; Zielińska, Agnieszka; Krogulec, Marek; Jeka, Sławomir; Wojciechowski, Rafał; Kolossa, Katarzyna; Dudek, Anna; Krajewska-Włodarczyk, Magdalena; Hrycaj, Paweł; et al. (Rheumatic & musculoskeletal diseases open, 2024)
ObjectivesTo demonstrate efficacy equivalence of CT-P47 and EU-approved reference tocilizumab (r-TCZ) in patients with rheumatoid arthritis (RA).MethodsThis double-blind, phase III study randomised (1:1) patients to receive CT-P47 or r-TCZ (8 mg/kg) every 4 weeks until week 20 during treatment period (TP) 1. Prior to week 24 dosing, patients receiving r-TCZ were randomised (1:1) to continue r-TCZ or switch to CT-P47; patients receiving CT-P47 continued CT-P47 (TP2, 8 mg/kg every 4 weeks until week 48). The dual primary endpoints (for different regulatory requirements) were mean changes from baseline in Disease Activity Score in 28 joints (DAS28; erythrocyte sedimentation rate (ESR)) at week 12 and week 24. Efficacy equivalence was determined if CIs for the treatment difference were within predefined equivalence margins: (95% CI −0.6, 0.6 (analysis of covariance (ANCOVA)) at week 12 or 90% CI −0.6, 0.5 (ANCOVA with multiple imputation) at week 24). Additional efficacy, pharmacokinetic (PK) and safety endpoints, including immunogenicity, were investigated. Findings up to week 32 are presented.ResultsIn TP1, 471 patients were randomised (234 CT-P47; 237 r-TCZ). The 95% and 90% CIs for the estimated treatment differences were contained within the predefined equivalence margins; the estimated difference in DAS28-ESR at week 12 was –0.01 (95% CI −0.26, 0.24) and at week 24 was −0.10 (90% CI −0.30, 0.10). Secondary efficacy endpoints, PKs and overall safety were comparable between groups up to week 32.ConclusionsEfficacy equivalence, alongside comparable PK, safety and immunogenicity profiles, was determined between CT-P47 and r-TCZ in adults with RA, including after switching from r-TCZ to CT-P47.